Urinary metabolites of the UV filter 2-Ethylhexyl salicylate as biomarkers of exposure in humans. (July 2019) - Bury, Daniel; Griem, Peter; Wildemann, Tanja; Brüning, Thomas; Koch, Holger M.
Highlights: Human urinary excretion kinetics of 2-ethylhexyl salicylate (EHS) after oral dosage. 7 metabolites identified, 3 metabolites unique to EHS investigated quantitatively. Urinary excretion fractions for these 3 specific EHS metabolites. ≥95% of these metabolites excreted within 24 h. Exemplary calculation of metabolite-based daily EHS intakes for a pilot population. Abstract: The UV filter 2-ethylhexyl salicylate (EHS) is used in sunscreens and other personal care products worldwide and has been found in a variety of environmental media. We aimed to provide human toxicokinetic data on EHS as a tool for risk assessment. For that purpose, we investigated metabolism and urinary metabolite excretion after a single oral EHS dose (57.4–75.5 μg/(kg body weight)) in three male volunteers. In a suspect screening, we tentatively identified seven EHS metabolites. Three EHS specific metabolites were quantitatively investigated: 2-ethyl-5-hydroxyhexyl 2-hydroxybenzoate (5OH-EHS), 2-ethyl-5-oxohexyl 2-hydroxybenzoate (5oxo-EHS), and 5-(((2-hydroxybenzoyl)oxy)methyl)heptanoic acid (5cx-EPS). These metabolites were excreted with urinary excretion fractions of 0.28% (range: 0.13−0.54%), 0.11% (0.06−0.20%), and 0.24% (0.14−0.41%), respectively. The elimination was fast: peak urinary concentrations were found 1.6–2.6 h after dose and ≥95% of the total amounts were excreted within 24 h. Elimination kinetics were biphasic, with mean elimination half-lives of 0.8 h (first phase) and 6.6 h (second phase) for 5OH-EHS, 0.8 h and 6.3 h for 5oxo-EHS, and 1.1 h and 5.9 h for 5cx-EPS. After dermal exposure (sunscreen application), we found a considerably delayed EHS elimination. Based on urinary metabolite levels we calculated EHS exposure levels for a small pilot population.